UPDATE OF THE CHECKLIST OF METAZOAN PARASITES OF FISHES FROM PERU: 2016 – 2021 - CENTURION, Nicole Edith (Ciência Animal, 2024)
An updated checklist of marine and freshwater fish parasitic metazoans of Peru: 2016-2021 is provided. The present review was carried out through a bibliographic search of scientific articles published in academic journals between 2016 - 2021, using databases such as Google Scholar, Scielo, ResearchGate, Elsevier, and Scopus. Data compilation was restricted to studies reporting metazoan parasites of fish in Peruvian waters. A total of 202 species of metazoan parasites were recorded in 103 fish species in Peru. The marine fish species with the highest parasitic record were Sarda chiliensis Cuvier, 1832 (n=23) and Paralabrax humeralis Valenciennes, 1828 (n=19). The freshwater fishes with the highest parasitic record were Colossoma macropomun Cuvier, 1818 (n=9), Sorubim lima Bloch & Schneider 1801, Brochis multiradiatus Orcés V., 1960, Brycon amazonicus Spix & Agassiz, 1829 and Osteoglossum bicirrhosum Cuvier 1829, each with five species reported. The metazoan parasite with the highest number of records was the larva of the cestode Adenocephalus pacificus Nybelin, 1931 (n=28). The diversity of metazoan parasites in Peruvian fish increased by 25,18% from 2016 to 2021.